İbn Ruşd’ün De Anima Üzerine Telhîs’inde İnsanın Akletme Yetisi. - Özkan, Abdussamet (Journal of Near East University Islamic Research Center / Yakın Doğu Üniversitesi İslam Tetkikleri Merkezi Dergisi)
According to Averroes, the human rational faculty (al-quwwa al-nāṭiḳa) serves human beings in both practical and theoretical matters through its twofold activity: from a practical point of view, it establishes many arts and professions that facilitate his life and satisfy the needs of his sensible existence with the help of intelligibles and judgments that he discovers through establishing connections between them, while from a theoretical point of view, it provides him with principles that do not address any of the needs of his sensible existence but enable his existence to reach perfection: In terms of these two fields of service it provides to man, the rational faculty of human soul is divided into two categories: first, the “practical intellect”(al-'aql al-'amalī) and second, the “theoretical intellect”(al-'aql al-naẓarī). The division of the faculty of intellection into practical and theoretical stems from the fact that the objects of cognition differ from each other in terms of their source. The activity of the practical intellect is realized through “artistic intentions” (bi-maʿānī ṣināʿīya mumkine), whereas the activity of the theoretical intellect is realized through “necessary intentions” (bi-maʿānī ḍarūriyya) whose existence does not depend on our will. The investigation of the practical intellect, according to Averroes, does not pose a great difficulty and is common to all human beings. The real problem arises in relation to the theoretical intellect, which rarely appears among human beings and appears as a highly divine faculty. At the center of Averroes' analysis of the human rational faculty in his Epitome on Aristotle's De anima is the problem of how humans, as material beings, can grasp immaterial intelligibles. Averroes seeks the answer to this fundamental question in the nature of the conjunction of the immaterial intelligibles to matter. Addressing this problem in the last part of his Epitome, Averroes solves it by isolating the activity specific to the rational soul and its object. That is, when analyzing the rational faculty of the human soul, he begins by examining the activity of the rational faculty and the nature of the intelligibles before the faculty itself. Averroes concludes that intelligibles have both a material and an immaterial aspect. The material part encompasses the role of the faculty of imagination, which is based on sensory experience and provides a kind of raw material for intellectual abstraction. Intelligibles based on the imagination are closely connected to the material world, since they originate from sensory data. The immaterial part of the intelligibles is the content that the intellect abstracts from these sensory experiences, and once abstracted, the intelligibles are no longer tied to specific material objects, but exist as universal concepts. Averroes explains this process by an analogy, where the disposition in the imaginative power is compared to a tablet that is waiting to be written upon as a foundation for receiving intelligibles (abstract ideas or universal concepts), while the intelligibles are likened to the inscriptions. This analogy reflects the passive nature of the human rational faculty in relation to intelligibles—just as a tablet does not generate writing but merely receives it, the soul and its imaginative power do not generate intelligibles but are prepared to receive them. Averroes identifies this disposition as one of the two subjects on which the intelligibles depend, which he calls the “first material intellect” (al-'aql al-ḥayūlānī alawwal). Thus, he sees the disposition in the imaginative forms that receive intelligibles as the first stage of human intellectual cognition. According to Averroes, it plays the role of both the subject of the intelligibles and the mover of intellection. The second is an eternal subject that he likens to the first matter, a pure potentiality that can take any form, just as the first matter accepts any sensory form in the material world. This eternal subject is the intellect, which represents the highest level of intellection, capable of reasoning and realizing intelligibles at all times.